AUDITOR CHARACTERISTICS AND TAX AVOIDANCE: THE MEDIATING EFFECT OF AUDIT QUALITY - Hendi, Hendi; Harsono, Budi; Silvana, Versia (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
Tax avoidance remains a major issue globally, including in Indonesia, as it directly impacts state revenues. This study examines the influence of auditor characteristics on tax avoidance (TAD), with audit quality (ADTQUA) as a mediating variable. Employing a quantitative approach, the research focuses on non-financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2024, comprising 1,428 samples. Data analysis was conducted using Eviews software, while the Sobel Test was applied to evaluate the mediating effect. The results reveal that auditor period (ADTPERIOD), industry specialisation (SPEC), and audit fees (ADTFEE) have a positive influence on audit quality. Furthermore, ADTPERIOD, SPEC, ADTFEE, and ADTQUA significantly and positively influence tax avoidance. The Sobel Test confirms that ADTPERIOD, SPEC, and ADTFEE indirectly affect TAD through ADTQUA. These findings indicate that auditor characteristics and audit quality play a crucial role in mitigating tax avoidance. The study provides empirical evidence beneficial to academic research and offers insights to policymakers for designing effective tax regulations aimed at reducing tax avoidance practices in Indonesia.JEL: H26, M42, M41.